2020
DOI: 10.1093/schbul/sbaa030.495
|View full text |Cite
|
Sign up to set email alerts
|

M183. Single-Session Dance/Movement Therapy for Thought and Behavioral Dysfunction Associated With Acute Schizophrenia: A Mixed Methods Feasibility Study

Abstract: Background Dance/movement therapy (DMT) interventions have been used to support people with schizophrenia; however, these typically include lengthier interventions. Current inpatient hospitalization lengths of stay do not offer the time needed to implement such interventions. The current treatment protocol for people in acute phases of schizophrenia is psychopharmacological; however, high rates of medication nonadherence and limited effects on negative symptomatology suggest the need for comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Research has shown a direct relationship between feelings of social exclusion with negative neurobiological responses (Lincoln et al, 2021;Metzl & Roberts, 2014). Beyond medical care, researchers have often excluded individuals with schizophrenia from their studies due to the presence of positive symptomatology or an exacerbation of symptomatology indicating they may be unable to manage the intervention or treatment (Biondo et al, 2021). This prevents people with schizophrenia from informing, testing, and responding to possible treatment protocols that could provide them with more effective care.…”
Section: Mental Health Disparitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has shown a direct relationship between feelings of social exclusion with negative neurobiological responses (Lincoln et al, 2021;Metzl & Roberts, 2014). Beyond medical care, researchers have often excluded individuals with schizophrenia from their studies due to the presence of positive symptomatology or an exacerbation of symptomatology indicating they may be unable to manage the intervention or treatment (Biondo et al, 2021). This prevents people with schizophrenia from informing, testing, and responding to possible treatment protocols that could provide them with more effective care.…”
Section: Mental Health Disparitiesmentioning
confidence: 99%
“…People with schizophrenia often have specific care needs due to movement dysregulations that are associated with their diagnosis (Biondo et al, 2021;Davis, 2019). The Diagnostic and Statistical Manual of Mental Disorders, Fifth edition (DSM-5) notes macro-level movement dysregulations such as holding bizarre postures or grossly disorganized movements (American Psychological Association [APA], 2013); however, there are many more subtle and disruptive bodily disturbances associated with schizophrenia including movement fragmentation, unsynchronized movement, subtle and bizarre facial expressions, or limited ability for spontaneous movements or gestures (Biondo et al, 2021;Davis, 2019).…”
Section: Body Symptomatologymentioning
confidence: 99%
See 2 more Smart Citations
“…Advancement of various antipsychotic medications have proven effective in lessening positive symptoms of schizophrenia, however, there are still indications for the need for complementary psychosocial treatment options. Research indicates that there are high levels of medication non-adherence rates associated with antipsychotic medication regimes due to many factors including: (1) difficulty obtaining the medication due to financial and accessibility concerns; (2) undesirable side effects; (3) stigmatization associated with taking antipsychotic medication; and (4) limited effects on negative symptoms of schizophrenia [19,20].…”
Section: Schizophrenia Spectrum Disorder Treatmentmentioning
confidence: 99%